MAKING ESSENTIAL AS AN EFFORT TO INCREASE BREAST MILK PRODUCTION THROUGH OXYTOCIN MASSAGE IN HERBAL VILLAGE, NGINDEN JANGKUNGAN SURABAYA - Tetty Rihardini; Setiana Andarwulan; Annah Hubaedah; Setiawandari Setiawandari (Yayasan Education and Social Center, 2021)
Oxytocin massage is a complementary treatment that can be used to increase breast milk production. Oxytocin massage is done by massaging the points on the back of the back. We do oxytocin massage to stimulate the letdown reflex in nursing mothers. In addition to oxytocin massage, increasing breast milk production can be done by using aromatherapy by utilizing natural herbal ingredients. The combination of oxytocin massage and the use of herbal aromatherapy will be more effective in producing breast milk. Next, we applied for a permit to carry out activities in the Nginden Jangkungan village. Then we started community service activities and taught how to do oxytocin massage and aromatherapy to the herbal village community in Nginden Jangungan village, Surabaya. We carry out community service with the title